Planejamento, síntese e avaliação do perfil quimioterápico de derivados tiossemicarbazônicos hibridizados a núcleos heterocíclicos - Albino, Sonaly Lima (2020)
Cancer and leishmaniasis are diseases associated with high rates of morbidity and mortality, with gaps in the therapeutic arsenal that underscore the progressive need for new chemotherapy drugs. The research and development of drugs that contain nitrogenous heterocyclic nuclei in their structure are increasingly targeted in Medicinal Chemistry due to their inherent potential. Therefore, this work proposed to design and synthesize twelve thiosemicarbazonic derivatives hybridized to different heterocyclic nuclei, to characterize them physically-chemically and structurally, to evaluate the interaction profile with potential in silico targets, to outline their in silico pharmacokinetic profile, to evaluate the antiproliferative activity against the tumoral and normal strains, determine their potential antileishmania against promastigote strains of Leishmania amazonensis and Leishmania infantum, as well as toxicity against human red blood cells in vitro. The designed compounds were evaluated in silico, through molecular docking, against the targets: topoisomerase IIα complexed with DNA (PDB ID: 5GWK), DNA (PDB ID: 1BNA and 1G3X) and topoisomerase I of L. donovani complexed with DNA (PDB ID: 2B9S), exhibiting a greater affinity of the acridinic compound, SOL-AC2, with the different isoforms of the topoisomerase enzyme and the appropriate DNA model for intercalator compounds, while the SOL-PR2 molecule showed a better profile when interacting with the DNA grooves. These derivatives were experimentally obtained by a condensation reaction between the thiosemicarbazide intermediates and the acridine, quinoline, indole, pyridine, phenyl-pyridine and phenyl-piperidine aldehydes, obtaining reaction yields ranging from 56.95% to 98.99%. These structures were confirmed by IR, ¹H NMR and ¹³C NMR spectroscopic techniquesIn vitro antiproliferative activity studies were performed through the MTT method, using five tumor lines (HCT 116, MCF-7, HeLa, SKMEL and PC-3) and two normal lines (L929 and HaCaT), in which the compound SOL-AC2 presented better antiproliferative activity, standing out due to the inhibition percentage of 75.20 ± 0.80% against the melanoma strain SKMEL, corroborating with the results in silico against the 5GWK and 1G3X targets. When evaluated in relation to their antipromastigote activity, indole compounds presented greater potential, especially the compound SOL-I1 (IC50 L. amazonensis = 12.16 µg mL^-1) ; IC50 L. infantum = 14.64 µg mL^-1). Therefore, possible mechanisms of action in silico have been proposed by the interaction with Leishmania targets: pyruvate kinase (PDB ID: 3PP7) and trypanothione reductase (PDB ID: 2JK6). From the results obtained, it was observed that maintaining the thiosemicarbazonic portion and modifying the heterocyclic nucleus, results in changes in the chemotherapy profile. These were also evaluated for their hemolytic activity, demonstrating that all compounds were non-toxic to red blood cells. In silico pharmacokinetic studies concluded that all compounds were consistent with druglikeness criteria established by Lipinski, Ghose and Egan, and showed good gastrointestinal absorption. Having obtained the most desirable molecular profile for each biological activity, novel analogous compounds were proposed based on the Topliss decision tree, evaluating them on the aforementioned crystallized targets. Most of them showed better affinity than the prototype compounds and desirable pharmacokinetic properties, enabling the synthesis and continuity of studies involving these.